The shtetl book an introduction to East European Jewish life and lore - Roskies, Diane K.; Roskies, David G. 1948- (KTAV, 1979)
Examines the history and way of life of Jews in Eastern Europe.
Keywords: Alltag, Brauchtum; Juden; Jews -- Europe, Eastern -- Social life and customs; Europe, Eastern -- Social life and customs